The Impact of Amniotic Fluid Interleukin-6, Interleukin-8, and Metalloproteinase-9 on Preterm Labor: A Narrative Review - Theodoros Karampitsakos; Despoina Mavrogianni; Nikolaos Machairiotis; Anastasios Potiris; Periklis Panagopoulos; Sofoklis Stavros; Panos Antsaklis; Peter Drakakis (Biomedicines)
Background/objectives: Preterm labor is a leading cause of neonatal morbidity and mortality worldwide. Previous research has indicated that an inflammatory response or microbial invasion of the amniotic cavity is a pathological condition linked to preterm birth; hence, inflammatory markers such as metalloproteinase-9 (MMP-9), interleukin-6 (IL-6), and interleukin-8 (IL-8) have been utilized to predict preterm delivery. The identification of reliable biomarkers for early prediction is critical for improving maternal, fetal, and neonatal outcomes. Methods: To address this issue, a literature review has been conducted on PubMed/Medline and Scopus databases for articles investigating the possible correlation between IL6, IL8, and MMP9 and preterm labor. Results: Using a comprehensive search of the PubMed and Scopus databases, 12 studies were analyzed to identify the correlation between these biomarkers and preterm labor. Seven studies point the impact of increased IL-6 levels or polymorphisms of the gene and higher incidence of preterm labor. Two of the included studies identified the increased risk for preterm birth in elevated levels of IL-8 in amniotic fluid. Six studies highlight the increased incidence of preterm birth in women with polymorphisms of the MMP-9 gene. Conclusions: Elevated IL-6 levels and specific gene polymorphisms are strongly associated with preterm delivery risk, with IL-8 concentrations correlating with systemic inflammation and histologic chorioamnionitis. MMP-9 gene variations and protein levels showed significant predictive value for membrane rupture and labor onset. The findings emphasize integrating these biomarkers into diagnostic tools for routine prenatal care, enhancing early detection, risk stratification, and timely interventions to improve maternal and neonatal outcomes.